2015
DOI: 10.1080/15459624.2015.1009984
|View full text |Cite
|
Sign up to set email alerts
|

Potential Dermal Exposure to Flonicamid and Risk Assessment of Applicators During Treatment in Apple Orchards

Abstract: Exposure and risk assessments of flonicamid for applicators were performed in apple orchards in Korea. Fifteen experiments were done with two experienced applicators under typical field conditions using a speed sprayer. In this study, cotton gloves, socks, masks, and dermal patches were used to monitor potential dermal exposure to flonicamid, and personal air samplers with XAD-2 resin and glass fiber filter were used to monitor potential inhalation exposure. The analytical methods were validated for the limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It involved no change in the usual conditions of work as most of the workers did not usually wear a coverall especially during application, no interference with usual working clothes and no thermal discomfort or limitation of movement [24]. This method was approved by the Organization for Economic Co-operation and Development (OECD) [25] and has been widely used in fruit-growing exposure studies [12,22,[26][27][28][29][30]. Eleven 10 × 10 cm patches were placed on the head (1 patch on a cap) and on different parts of the body directly on the skin: the arms (2 patches), forearms (2 patches), chest (1 patch), back (1 patch), thighs (2 patches) and lower legs (2 patches) (Appendix A, Figure A1).…”
Section: Observations Of Farm Operators and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It involved no change in the usual conditions of work as most of the workers did not usually wear a coverall especially during application, no interference with usual working clothes and no thermal discomfort or limitation of movement [24]. This method was approved by the Organization for Economic Co-operation and Development (OECD) [25] and has been widely used in fruit-growing exposure studies [12,22,[26][27][28][29][30]. Eleven 10 × 10 cm patches were placed on the head (1 patch on a cap) and on different parts of the body directly on the skin: the arms (2 patches), forearms (2 patches), chest (1 patch), back (1 patch), thighs (2 patches) and lower legs (2 patches) (Appendix A, Figure A1).…”
Section: Observations Of Farm Operators and Sample Collectionmentioning
confidence: 99%
“…Großkopf explained that cleaning was not considered as a modeling factor since its impact on exposure had not been demonstrated in studies included in the AOEM [11]. However, owing to contact with the contaminated surfaces of the spraying equipment [39], this final step has proven to create significant exposure in operators [15], increasing urinary levels of metabolites [27,38]. Overall, it was even found to be the phase with the most exposure in the CANEPA study [20].…”
Section: External Validitymentioning
confidence: 99%
“…Studies have shown that flonicamid is less toxic to bees, honeybees and natural predators of insect pests compared with neonicotinoid insecticides and was recommended for widespread pest control (Zhao et al . 2015; Kodandaram et al . 2017; Abbas et al .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with neonicotinoid insecticides, studies have shown that flonicamid is less toxic to bees, honeybees, and natural predators of insect pests; hence, it was recommended for widespread pest control. 2,7,14,15 However, despite having decreased toxicity and being responsible for lower levels of residue buildup in the environment compared with neonicotinoid insecticides, flonicamid toxicity against predators of insect pests has been reported. For example, flonicamid was found to be toxic to coccinellid and chrysoperla, predators of pomegranate aphids, 16 while a 17.39% mortality rate was observed in adult Coccophagus japonicus wasps following exposure to flonica-mid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Globally, neonicotinoids are the most commonly used class of insecticides; however, they pose a significant risk to wild bees and honeybees. Therefore, several countries have banned the use of neonicotinoid insecticides, necessitating the development of alternative pest control products. Compared with neonicotinoid insecticides, studies have shown that flonicamid is less toxic to bees, honeybees, and natural predators of insect pests; hence, it was recommended for widespread pest control. ,,, …”
Section: Introductionmentioning
confidence: 99%